2013
DOI: 10.1016/j.jbiosc.2013.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Production of ethanol from mannitol by the yeast strain Saccharomyces paradoxus NBRC 0259

Abstract: Mannitol is a promising marine macroalgal carbon source. However, organisms that produce ethanol from mannitol are limited; to date, only the yeast Pichia angophorae and the bacterium Escherichia coli KO11 have been reported to possess this capacity. In this study, we searched a yeast strain with a high capacity to produce ethanol from mannitol and selected Saccharomyces paradoxus NBRC 0259 for its ability to produce ethanol from mannitol. This ability was enhanced after a 3-day cultivation of this strain in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 22 publications
(32 reference statements)
1
36
0
1
Order By: Relevance
“…The growth of MK3619 and MK3683 on SM plates was dependent on functional mitochondria and oxygen (see Fig. S1 in the supplemental material), confirming that assimilation of mannitol requires respiration, as reported previously (11,13).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…The growth of MK3619 and MK3683 on SM plates was dependent on functional mitochondria and oxygen (see Fig. S1 in the supplemental material), confirming that assimilation of mannitol requires respiration, as reported previously (11,13).…”
Section: Resultssupporting
confidence: 87%
“…We recently reported that S. paradoxus NBRC0259-3 is the most suitable yeast strain for the production of ethanol from mannitol and is superior in this regard to two other microbes, P. angophorae and E. coli KO11 (11). Therefore, we compared the salt tolerances of MK4416 and MK4456 strains with that of S. paradoxus NBRC0259-3, P. angophorae, and E. coli KO11.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations